Sweet Wooden Stem Leather (Cinnamomum burmanii) Assessed From Effective Extraction and Dosage Methods For Diabetes (Literature Review) - Septana Nur Hidayat; Endang Setyaningsih (Institut Agama Islam Negeri Kerinci, 2021)
Cinnamon contains flavonoid compounds that can reduce diabetes blood glucose levels. Diabetes is a group of metabolic disorders characterized by impaired glucose metabolism. The use of injectable or oral chemical drugs is relatively expensive and produces side effects. One class of secondary metabolite compounds that can treat diabetes mellitus is flavonoids. One of the plants that contain flavonoids is Cinnamomum burmanii. The purpose of this study was to examine the extract of Cinnamomum burmanii stem bark in terms of the extraction method and the effective dose against diabetes. The method used is to study 33 selected articles to obtain 5 national journals, 10 international journals, and 8 indexed journals, totaling 23 articles. The results of the identification of 23 scientific articles show that the use of doses in the range 1-200 mg / kgBW by the maceration extraction method is 39.13%. The conclusion obtained from this review literature is that the use of cinnamon bark extract (Cinnamomum burmanii) by maceration method in the dose range 1-200 mg / kgBW can be used to reduce diabetes blood glucose levels